The effect of health literacy on health investment intention: a cross-sectional study among petrochemical employees in China - Delong Wang; Ying Wang; Huifen Ma; Shichao Zhao (Frontiers Media S.A., 2024)
BackgroundsIn the petrochemical industry, employees are exposed to various health hazards, which pose serious challenges to their health and hinder the sustainable development of the petrochemical industry. Investing in health has proved a potential strategy to enhance general health. However, global health investment is notably insufficient, mainly due to the public's limited intention to invest in their health. While past research has identified various determinants of health investment intentions, the relationship between health literacy and health investment intention remains somewhat controversial and needs more empirical validation.ObjectivesThis study aims to assess the level of health literacy and health investment intention among employees in one of China's largest petrochemical companies and to explore the effect of health literacy on health investment intention.MethodsA cross-sectional study was conducted in a petrochemical company. The valid sample size for this study was 39,911 respondents. Data were collected using a designed questionnaire, including socio-demographic information, questions about health investment intention, and the "2020 National Health Literacy Monitoring Questionnaire." Several statistical analysis methods were employed, including descriptive analysis, Chi-square test, logistic regression, and multiple linear regression.ResultsThe study disclosed an average health literacy score of 56.11 (SD = 10.34) among employees, with 52.1% surpassing the qualification threshold. The "Chronic Disease" dimension exhibited the lowest qualification rate at 33.0%. Furthermore, 71.5% of the employees expressed an intention to invest in health, yet a significant portion (34.5%) opted for the minimal investment choice, less than 2,000 RMB. Logistic regression analysis indicated a positive correlation between health literacy and health investment intention (OR = 1.474; p < 0.001). This association's robustness was further indicated by multiple linear regression analyses (β = 0.086, p<0.001).ConclusionThe employees' health literacy significantly exceeds the national average for Chinese citizens, yet the qualified rate in the "Chronic Disease" dimension remains notably low. A majority of employees have the intention to invest in health, albeit modestly. Furthermore, while health literacy does positively influence health investment intention, this effect is somewhat limited. Accordingly, personalized Health education should be prioritized, with a focus on improving chronic disease knowledge and facilitating the internalization of health knowledge into health beliefs.